PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE OUTSIDE CIRCLE UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII2 SMPN 2 PEKANBARU TAHUN PELAJARAN 2011/2012 - Darmawati '; Imam Mahadi; Ria Syafitri (Biogenesis, 2012)
Classroom Action Research has been conducted (PTK), which aims to improve the scientific attitude and learning outcomes of students with models of biological types of cooperative learning on the inside outside circle VIII2 grade students at SMPN 2 pekanbaru. The study was conducted from October to November 2011. The study subjects were 36 students (16 male and 20 female). Parameter were the attitude of scientific research, the study (absorption and completeness of student learning), award groups, and advocates parameter is the student activity and teacher activity. Data were analyzed descriptively. The results indicate that the cycle I mean the scientific attitude of students is 79.94% (Fair), the average absorption of students is 79.78% (Enough), which is 75% learning completeness (Enough), which gained the award there is a super predicate group, the average activity of students is 81.13% (Fair), the average results of activity of the teacher is 90.91% (Good). While on average the second cycle of scientific attitude of students increased to 90.32% (Good), the average absorption of students is 87.58% (Good), exhaustiveness study is 100% (Very good), which achieved full appreciation super group there are 2 groups , the average student activity increased to 90.21% (Good), the average activity of the teacher is 100% (Very good). From the research results can be concluded that with the implementation of cooperative learning model of the type of inside outside circle can increase the scientific attitude and learning outcomes VIII2 grade biology students SMPN 2 Pekanbaru.Keywords: Biology Learning Outcomes, Cooperative Learning Model Type Inside Outside Circle, scientific attitude,